Theoretical and practical knowledge on fire safety standards in shopping malls in Huancayo - Junín 2016. - Lenin Miguel Bendezú Romero, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to determine the level of knowledge of fire safety standards by those attending shopping malls in the city of Huancayo. Currently, in the city of Huancayo there are shopping malls that concentrate businesses and therefore the population who go to these places for two purposes: to acquire all kind of goods and for recreation. In this sense, the population needs to be aware of the dangers to which they are exposed, as well as being aware of the high probability of the presence of a fire, especially the owners of these shopping malls, who could be affected with substantial losses in monetary value, as well as the loss of human lives. This research analyzes the level of practical theoretical knowledge that people who go to these malls have and what to do so that these people adopt this knowledge, for which the type of research to be applied is developed being applied - observational - comparative, where a sample population is taken in order to perform an analysis regarding this research. It has been found that a large percentage of the surveyed population does not know the fire safety standards in shopping centers. This is attributed to various causes including the socio-cultural level of the population under study, although the results regarding the theoretical and practical knowledge of fire safety in shopping malls in Huancayo are not encouraging, it asks to develop more work and join efforts in order to raise awareness among our population. This research work will be of great importance since it will help to change the thinking of people who go to these shopping centers in the city of Huancayo.